Interrelationship between endotoxicosis and syndrome of intraabdominal hypertension in pathogenesis of abdominal sepsis. - N. A. Valiyev (Клінічна хірургія, 2022)
Objective. Studying of mutual role of the main pathogenetic factors of abdominal sepsis – the inflammation origin and intraabdominal hypertension, from the one side, endotoxicosis and the abdominal compression syndrome (ACS), from the other side.